Autotaxin upregulated by STAT3 activation contributes to invasion in pancreatic neuroendocrine neoplasms. Issue 12 (December 2018) - Yang, Linfei; Yu, Xiao; Yang, Yongchao
Abstract : Although the upregulation of autotaxin (ATX) is associated with many solid tumours, its role in pancreatic neuroendocrine neoplasms (pNEN) has not been well elucidated. The expression of ATX in pNEN tissues and pNEN cell line BON1 was analysed by Western blot, PCR and immunocytochemistry upon exposure to interleukin-6 (IL-6). Additionally, pNEN cell line BON1 was transfected with siRNAs against ATX or signal transducer and activator of transcription 3 (STAT3) and assessed by in vitro invasion assays. The following results were obtained. The expression of ATX in pNEN tissues was significantly increased compared with that in normal pancreatic tissues. High ATX expression was strongly correlated with tumour grade, lymph node metastasis and tumour-node-metastasis stage. Furthermore, ATX downregulation notably inhibited the metastatic capacity of pNEN cells, whereas STAT3 knockdown was found to downregulate the expression of ATX. ATX expression was upregulated in BON1 cells upon stimulation with IL-6, and this was accompanied by activation/phosphorylation of STAT3. Western blot analysis of human pNEN tissue extracts confirmed increased ATX expression and STAT3 phosphorylation with elevated expression levels of IL-6. In conclusion, ATX is upregulated in pNEN and is correlated with the metastatic capacity of pNEN cells, potentially via interaction with STAT3 activation.